Italian Psychology and Jewish Emigration under Fascism From Florence to Jerusalem and New York - Guarnieri, Patrizia; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
.
1 Psychologists (3z(Bin the true sense of the word(3y (B-- 2 Neo-idealism and (3z(Bthe Cinderella of the sciences(3y (B-- 3 Fascistization discrimination and persecution -- 4 The Zionist network and Enzo Bonaventura in Jerusalem -- 5 The antifascist network and Renata Calabresi in New York. .s
Keywords: History; History; History, general; Electronic books